2019
DOI: 10.3390/socsci8110315
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom to Improve University Student Centered Learning and Academic Performance

Abstract: In recent years, educational research has focused on analyzing significant differences in the academic performance of university students according to the intervention model of the traditional methodology vs. the flipped classroom. This empirical-analytical research is based on a quasi-experimental design with non-equivalent groups. The results reveal significant differences on the average grades of university students; those participating in the flipped classroom obtained higher scores than students following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
2
21
0
4
Order By: Relevance
“…García-Peñalvo (2020) indicated that, although the digitization of the Spanish university began a decade ago, we have focused on face-to-face teaching. However, in this time of isolation, it is necessary to integrate technology into classrooms ( Mingorance et al, 2019 ). But any change generated many uncertainties in the university context.…”
Section: Introductionmentioning
confidence: 99%
“…García-Peñalvo (2020) indicated that, although the digitization of the Spanish university began a decade ago, we have focused on face-to-face teaching. However, in this time of isolation, it is necessary to integrate technology into classrooms ( Mingorance et al, 2019 ). But any change generated many uncertainties in the university context.…”
Section: Introductionmentioning
confidence: 99%
“…Flipped classroom is a new teaching methodology, which has received recognition in primary, secondary and higher educational institutions. The essence of it is that lectures are held outside the classroom, study time is devoted to solving problems, the teacher has a role of trainer and facilitator [30][31][32] The course can include-(a) a content module-a section of educational materials, which contains web-links to the necessary resources on the topic under study, tests; (b) a help module in the form of a tooltip, a dialog box, a text file; (c) an interactive module-mail, small forum, chat, electronic conference, video conference and so forth; (d) an administrative module for managing the group [33]. For distance learning, researchers used the following tools and methods: paper books, online electronic educational publications, computer training systems in hypertext and multimedia versions, audio and video educational and information materials, laboratory remote workshops, simulators with remote access, information databases, electronic libraries with remote access and so forth [34].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the pre-class content is in the form of pre-recorded lectures or screencast [21]. Other methods of pre-class content dissemination include readable contents, Blogs, and Google Docs [22].…”
Section: B Importance Of Interactive Classroom In Class Activities: mentioning
confidence: 99%